An overview of the progress and challenges of peatland restoration in Western Europe. Issue 2 (17th August 2016) - Andersen, Roxane; Farrell, Catherine; Graf, Martha; Muller, Francis; Calvar, Emilie; Frankard, Philippe; Caporn, Simon; Anderson, Penny
Abstract: Peatlands are the most efficient terrestrial carbon store on Earth, and deliver multiple other ecosystem services including climate regulation, water purification, preservation of ecological and archaeological records, etc. Disturbed and degraded peatlands do not provide the same ecological services and thus bear a significant cost to society. Because this cost may be alleviated by appropriate restoration measures, money is being invested in peatland restoration projects around the world. Here, we review over 25 years of restoration in Western Europe. First, we provide an overview of techniques used in different contexts and evaluate the status of the evidence base for restoration outcomes. Between 1993 and 2015, the EU‐LIFE nature programme alone invested 167.6M € in 80 projects, which aim to restore over 913 km 2 of peatland habitats in Western European countries, mostly in protected sites part of the Natura 2000 EU network. This represents less than 2% of the total remaining area of peatlands in these countries, most of which have been impacted to some degree by anthropogenic disturbances. Potential for restoration should be considered in nondesignated sites. We reviewed a number of case studies covering a range of restoration approaches used in different parts of Western Europe. We found that published evidence of restoration progress was limited to specific sites/areas, and in many cases lacked baseline measurements and clear goals, that is, measurable target or contemporary reference(s). We discuss barriers and opportunities to turn the tide for peatland restoration in Western Europe and promote the establishment of robust, standardized monitoring schemes.